Efektivitas Program Serbu sebagai Upaya Peningkatan Literasi di Sekolah Dasar - Dian Fadillah; Baiq Hariyana; Ayatun Nufus; Dahlia; Alfin Tulhidayah; Syafruddin Muhdar (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the effectiveness of the “Serbu Literasi” Program in improving elementary school students’ literacy skills. The research employed a quantitative approach using a quasi-experimental design in the form of a one-group pre-test and post-test. The subjects were 23 third-grade students of SDN 2 Labuapi. The research instruments consisted of a literacy test and an observation sheet. The data were analyzed using descriptive statistics and a normality test as supporting analysis. The results showed an increase in the students’ average score from 66.30 in the pre-test to 85.65 in the post-test. The statistical test also indicated a significant difference between students’ abilities before and after the treatment. Thus, the Serbu Literasi Program is proven to be effective in improving elementary school students’ literacy skills. The program also enhances student engagement, reading interest, and critical thinking skills in understanding information.